Emerging voice: Exploring the process of teacher-students’ dialogic interaction in mobile instant messaging (MIM) to construct voice in argumentative writing - Latipah, Yeni; Gunawan, Wawan (Indonesian Journal of Applied Linguistics, 2021)
Despite the growing body of literature on the role of Mobile Instant Messaging (MIM) in supporting educational practice, little comprehensive understanding could be gained on how to scrutinize dialogue between teacher and students in MIM for the sake of students’ meaning-making. Thus, this study explored the process of teacher-students dialogic interaction in a MIM group as a viable pedagogical activity in fostering students’ establishment of voice in argumentative writing. Particularly, it focused on the construction of Engagement resources (Martin White, 2005) as the realization of voice in the students’ writing. To reach the objectives, a qualitative case study with multiple data sources were employed, i.e., the records of instant messaging conversation, students’ argumentative text, interview, and observation. The findings revealed that the teacher-students’ discussions in the instant messaging space were enjoyable activities that could support the students’ awareness of Engagement resources because they allowed the discovery of repertoires through reasoning, problem-solving, and peer learning. Furthermore, although there were various uptakes of Engagement resources in the students’ text, most students showed progressive achievements in applying the sources effectively in their writing.